The unknown immigration: incentives and family composition in intercountry adoptions to the United States - Fernando Antonio Lozano; Sherrie A. Kossoudji (Institute for the Study of Labor (IZA), 2009)
Children adopted from abroad are an immigrant group about which little is known. According to the U.S. Census more than one and a half million children living in the U.S. are adopted, with fifteen percent of them born abroad. In fact more than twenty thousand adopted orphans from abroad enter the country each year. The families who adopt these orphans are mostly white, wealthy, and well educated (Kossoudji, 2008). What are the characteristics of children who are adopted from abroad and what incentives drive families to adopt them? In this paper we use the 2000 census to illuminate the landscape of international adoption. We address three issues: 1) How do the demographic characteristics of the children adopted from abroad change as other countries open and shut the door to inter-country adoptions, changing the supply of available children? 2) U.S. born parents and foreign-born parents may have different incentives to adopt. How are these incentives reflected in the characteristics of the children they adopt? 3) What explains differences in the estimates of foreign-born adopted children in the Census and the number of visas granted by the State Department?
Keywords: J13; J12; 330; Immigrant children; international adoption; Kinder; Einwanderung; Familienrecht; Familiensoziologie; USA